Functional Statistics Outliers Detection and Quality Control - Martínez Torres, Javier (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Functional analysis, the branch that lies between mathematical analysis and statistics, has many applications in the field of engineering and processes. Thus, this book presents several applications carried out from this perspective, as well as various works of a theoretical nature that take a further step so that researchers can use these models with high precision.